2004
DOI: 10.1364/opex.12.006122
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon fluorescence microscope with a hollow-core photonic crystal fiber

Abstract: Self-phase-modulation and group velocity dispersion of near IR femtosecond pulses in fibers restrict their use in two-photon fluorescence microscopy (TPFM). Here we demonstrate a hollow-core photonic crystal fiber based two-photon fluorescence microscope with low nonlinearity and dispersion effects. We use this fiber-based TPFM system to take two-photon fluorescence (chlorophyll) images of mesophyll tissue in the leaf of Rhaphidophora aurea. With less than 2mW average power exposure on the leaf at 755nm, the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Moreover, within the transmission window of PBF, which is called the bandgap and usually covers a spectral range of several tens to over a hundred nanometers, there is usually a wavelength at which group velocity (chromatic) dispersion vanishes (Box 1). Pulses centered at this wavelength scarcely suffer any broadening, making PBF an excellent choice for pulse delivery 16,17,38,53,54 . For other transmitted wavelengths only tens of nanometers away, however, dispersive pulse broadening can be more severe than in conventional SMF.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, within the transmission window of PBF, which is called the bandgap and usually covers a spectral range of several tens to over a hundred nanometers, there is usually a wavelength at which group velocity (chromatic) dispersion vanishes (Box 1). Pulses centered at this wavelength scarcely suffer any broadening, making PBF an excellent choice for pulse delivery 16,17,38,53,54 . For other transmitted wavelengths only tens of nanometers away, however, dispersive pulse broadening can be more severe than in conventional SMF.…”
mentioning
confidence: 99%
“…The simplest application of fiber-optics in microscopy is remote delivery of light [8][9][10][11][12][13][14][15][16] , which allows the excitation light source or photodetectors to reside apart from a conventional microscope. Optical fiber also enables miniaturized or compact forms of microscopy for portable usage 1, 17 , 18.…”
mentioning
confidence: 99%
“…It has been shown that with the same pulse energy, the excitation efficiencies of TPF and SHG are inversely proportional to the pulse width, s (Shen, 1984, Boyd, 1992, Yariv, 1997, Myaing et al, 2000Tai et al, 2004). The pulse-width measurement experimental setup is shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the degradation of multiphoton and multiharmonic excitation efficiencies, few groups (Flusberh et al, 2005;Göbel et al, 2004;Myaing et al, 2006;Piyawattanametha et al, 2006) have demonstrated fiber-based beam-scanning nonlinear endoscopes. The degradation of nonlinear excitation efficiency comes from temporal broadening of femtosecond pulses inside optical fibers (Clark et al, 2001;Myaing et al, 2000;Tai et al, 2004), where pulse broadening originates from the fiber dispersion and nonlinear effects. Recently, several groups have recovered the excitation efficiency by precompensating the group velocity dispersion and lowering the nonlinear effects with a grating pair at the fiber's entrance (Clark et al, 2001;Göbel et al, 2004;Myaing et al, 2000Myaing et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent this problem specialty optical fibers are used for the transport of such high-peak-power ultra-short pulses. Some of these fibers are photonic crystal fibers (PCFs) [3,4], rod-type fibers [5], and fewmode fibers [6,7,8]. PCF can show efficient single-mode operation and can maintain good beam quality in the output pulses.…”
Section: Introductionmentioning
confidence: 99%